Macroscopic diagnostic clue for parkinsonism. Issue 5 (22nd August 2022) - Yoshida, Mari; Akagi, Akio; Miyahara, Hiroaki; Riku, Yuichi; Ando, Takashi; Ikeda, Toshimasa; Yabata, Hiroyuki; Moriyoshi, Hideyuki; Koizumi, Ryuichi; Iwasaki, Yasushi
Abstract : The neuropathological background of parkinsonism includes various neurodegenerative disorders, including Lewy body disease (LBD), multiple system atrophy (MSA), progressive supranuclear palsy (PSP), and corticobasal degeneration (CBD). The pathological diagnostic procedure begins by assessing the macroscopic findings to evaluate the degenerative lesions in brains with the naked eye. Usually, degenerative lesions show variable atrophy and brownish discoloration in accordance with disease‐specific profiles. These macroscopic appearances support neuropathologists in identifying the relevant regions for microscopic examination. The neuropathological diagnosis of parkinsonism is based on regional distribution and fundamental proteinopathies in neurons and glia cells. LBD and MSA are synucleinopathies, and PSP and CBD are tauopathies. Among them, glial‐predominant proteinopathy (MSA, PSP, and CBD) may play a significant role in volume reduction. Therefore, macroscopic inspection provides the appropriate direction for assessment. The disease duration, the severity of lesions, and mixed pathologies make the validation of macroscopic observations more complicated. In this review, we outline the macroscopic diagnostic clues in LBD, MSA, PSP, and CBD that could help with pathological refinement.